Synthesis and electrical characterization of CaBi2Nb2O9 thin films deposited on Pt/Ti/SiO2/Si substrates by polymeric precursor method - Simoes, A. Z.; Ramirez, M. A.; Riccardi, C. S.; Gonzalez, AHM; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2006)
We report the successful deposition of CaBi2Nb2O9 (CBN) thin films on platinum coated silicon substrates by polymeric precursor method. The CBN thin films exhibited good structural, dielectric and CBN/Pt interface characteristics. The leakage current of the capacitor structure was around 0.15 A cm(-2) at an applied electric field of 30 kV cm(-1). The capacitance-voltage measurements indicated good ferroelectric polarization switching characteristics. The typical measured small signal dielectric constant and the dissipation factor at a frequency of 100 kHz were 90 and 0.053, respectively. The remanent polarization and the drive voltage values were 4.2 C cm(-2) and 1.7 V at an applied voltage of 10 V. No significant fatigue was observed at least up to 10(8) switching cycles. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: thin films; annealing; electrical properties